2019
DOI: 10.1021/acs.analchem.8b04671
|View full text |Cite
|
Sign up to set email alerts
|

Ti-Catalyst Biomimetic Sensor for the Detection of Nitroaromatic Pollutants

Abstract: An electrode modified by a Ti complex in Nafion ® was used in the electrochemical detection of nitroaromatic compounds (NACs). The catalyst reduces nitroaromatic groups by a 6-electron process and with a high apparent rate constant k 1 that was estimated to be at least 19000 mol -1 L s -1 by simulation of the first step of the cathodic reduction of 4-nitrophenylacetic acid used as model molecule. The modified electrode was prepared and optimized in terms of Nafion ® and catalyst concentrations. In the chosen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Under the optimal detection conditions (Figure S18), the fluorescence at 545 nm decreased linearly with the logarithm of the concentration ranging from 0.01 to 500 μM (Figure B and C), demonstrating the capacity of this composite for quantitative analysis in this concentration range. The limit of detection (LOD) was calculated to be 5.6 nM (S/N = 3), which was 3 orders of magnitude lower than Tb-MOF, and superior to many other reported electrochemical and optical methods (Figure D). Moreover, the color decay could even be distinguished by the naked eye when DNT was increased from 0 to 500 μM (inset in Figure C), indicating the potential of the probe for rapid colorimetric detection on site. The Tb-PGO-COOH probe also showed high selectivity to DNT, even though the concentrations of the interfering species were 10 fold that of DNT (Figure S19).…”
Section: Resultsmentioning
confidence: 85%
“…Under the optimal detection conditions (Figure S18), the fluorescence at 545 nm decreased linearly with the logarithm of the concentration ranging from 0.01 to 500 μM (Figure B and C), demonstrating the capacity of this composite for quantitative analysis in this concentration range. The limit of detection (LOD) was calculated to be 5.6 nM (S/N = 3), which was 3 orders of magnitude lower than Tb-MOF, and superior to many other reported electrochemical and optical methods (Figure D). Moreover, the color decay could even be distinguished by the naked eye when DNT was increased from 0 to 500 μM (inset in Figure C), indicating the potential of the probe for rapid colorimetric detection on site. The Tb-PGO-COOH probe also showed high selectivity to DNT, even though the concentrations of the interfering species were 10 fold that of DNT (Figure S19).…”
Section: Resultsmentioning
confidence: 85%
“…The detection of nitroaromatics in recent years has attracted extensive attention because these types of compounds are explosive, posing a threat to public safety. Compared with traditional detection methods (such as LC–MS, GC–MS, and HPLC), the fluorescence method has some advantages, such as high sensitivity, speediness, and easy operation. Among these chemosensors, the forces acting between the host and guest are mostly hydrogen bonds (such as N–H···O, O–H···O, and C–H···O). Hence, it is a meaningful work to design and synthesize hosts with active hydrogen atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the characteristics mentioned above, Nafion has been widely studied and used in electrochemistry field for several decades as a conventional membrane used in the fuel cell application 2,3 . In recent years, its application in other fields is also attempted, such as, sensors, 4–6 catalysis, 7–9 medicine, 10,11 pervaporation, 12,13 and gas separation 14–20 …”
Section: Introductionmentioning
confidence: 99%
“…Owing to the characteristics mentioned above, Nafion has been widely studied and used in electrochemistry field for several decades as a conventional membrane used in the fuel cell application. 2,3 In recent years, its application in other fields is also attempted, such as, sensors, [4][5][6] catalysis, [7][8][9] medicine, 10,11 pervaporation, 12,13 and gas separation. [14][15][16][17][18][19][20] The first comprehensive study on the gas permeation in a Nafion membrane was reported by Chiou and Paul 21 and it was found that the membrane had high separation factors for He/CH 4 , He/H 2 , and N 2 /CH 4 relative to other polymeric membranes, appearing to offer some attractive features for these gas pairs.…”
Section: Introductionmentioning
confidence: 99%